Fobia Wajib Pajak Untuk Mengungkapkan Harta - Fellyana Nadia Putri; Umaimah Umaimah (JIATAX (Journal of Islamic Accounting and Tax), 2021)
This study aims to reveal the meaning of phobia that is felt by taxpayers in disclosing their assets. This study used a qualitative method with a transcendental phenomenological approach by Edmund Huserl. The number of informants in this study were 3 people including taxpayers, tax authorities and tax consultants. To form informant awareness, data collection was carried out by conducting in-depth interviews with the three informants. The meaning of the phobia revealed is that the taxpayer's phobia in disclosing assets is a form of calculation of profit and loss and a reflection of the taxpayer's faith.